The Pandemic and Media Discourse: Linguistic Framing of Covid-19 in Egyptian Advertisements - Nohayer E. Lotfy (Yayasan Visi Intan Permata, 2023)
Since the outbreak of Covid-19 in late 2019, media discourse worldwide has attempted to frame the pandemic as an invisible enemy everyone needs to fight. The total lockdown that took place due to the pandemic has also had an impact on media discourse in its different forms, such as television commercials. Business companies have tried to address the theme of the pandemic and the urgency to abide by the lockdown and social distancing in their advertisements produced during the period of 2019-2020. This paper aimed to examine selected Egyptian commercials, either on television or YouTube, to analyze how they tackled the pandemic. Eight Egyptian commercials were analyzed, focusing on how the pandemic was framed verbally and visually. Analysis was carried out on two levels. The first level was concerned with examining the ideas/themes that were promoted in the selected commercials that would shape how the audience would regard the pandemic. The second level investigated how these themes were represented verbally and visually by analyzing the linguistic as well as the visual layout used in the selected commercials. Significant results showed that the pandemic was linguistically framed in metaphors related to war, enemy, family, and Lockdown/Stay Home. These linguistic frames were also supported by the visual representation that highlighted the themes of social distancing and the lockdown.